Intergenerational transmission of unemployment after apprenticeship graduation: does parental socioeconomic background still matter? - Sandra Dummert [Verfasser] (My University, 2024)
„A smooth transition from apprenticeship to standard employment is a key step in the professional biographies of apprenticeship graduates. In this study, the transition of apprenticeship graduates from households that receive unemployment benefits are considered. These graduates are thought to be disadvantaged because their parents’ socioeconomic background is assumed to influence their employment outcomes through processes of intergenerational transmission and cumulative disadvantage. Based on administrative data from the Sample of Integrated Welfare Benefit Biographies (SIG) provided by the Institute for Employment Research (IAB), this analysis offers deeper insights into parental socioeconomic background and the individual factors that affect the risk of unemployment following the completion of an apprenticeship. In the case of an unsuccessful direct transition to standard employment, the factors influencing the duration of the first unemployment are also assessed. The results show that, as with individual characteristics, parents’ education level has a significant effect on the graduates’ risk of unemployment. The duration of the household’s benefit receipt, on the other hand, significantly influences the duration of the first unemployment in the case of an unsuccessful transition following an apprenticeship.“ (author’s abstract; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; 370; 300; Berufseinmündung; Zweite Schwelle; Auszubildender; Sozioökonomischer Status; Eltern; Arbeitslosigkeit; Arbeitslosengeld; Einflussfaktor; Arbeitsmarktrisiko; Benachteiligung